2006
DOI: 10.1063/1.2216435
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen resistive double-side (Pb0.72La0.28)Ti0.93O3 buffered Pb(Zr0.52Ti0.48)O3 thin films

Abstract: The hydrogen annealing effect and the fatigue resistance of the Pb(Zr0.52Ti0.48)O3 (PZT) thin films with double-side (Pb0.72La0.28)Ti0.93O3 (PLT) buffer layers were investigated. With the PLT buffer layers, the films showed better hydrogen resistance than the PZT films because of the enhancement of the structural properties of the double-side PLT buffered PZT films. This structure also exhibited good fatigue endurance after 109 switching cycles even without oxide electrodes, mainly because the accumulated char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Lee et al reported that the PZT structure (Au=PZT=Pt=Ti=SiO 2 = Si) undergoes serious degradation after H 2 annealing, while the PLT=PZT=PLT structure (Au=PLT=PZT=PLT=Pt=Ti= SiO 2 =Si) does not. 28) Liang et al also reported that a Pt= PZT=BaPbO 3 (BPO) capacitor (Pt=PZT=BPO=Pt=Ti=SiO 2 = Si) suffered severe degradation of ferroelectricity under 3% H 2 =balance N 2 gas annealing at temperatures as low as 175 °C. 34) By contrast, no obvious degradation of BPO=PZT= BPO capacitor (BPO=PZT=BPO=Pt=Ti=SiO 2 =Si) is seen under 3% H 2 =balance N 2 gas annealing at 400 °C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al reported that the PZT structure (Au=PZT=Pt=Ti=SiO 2 = Si) undergoes serious degradation after H 2 annealing, while the PLT=PZT=PLT structure (Au=PLT=PZT=PLT=Pt=Ti= SiO 2 =Si) does not. 28) Liang et al also reported that a Pt= PZT=BaPbO 3 (BPO) capacitor (Pt=PZT=BPO=Pt=Ti=SiO 2 = Si) suffered severe degradation of ferroelectricity under 3% H 2 =balance N 2 gas annealing at temperatures as low as 175 °C. 34) By contrast, no obvious degradation of BPO=PZT= BPO capacitor (BPO=PZT=BPO=Pt=Ti=SiO 2 =Si) is seen under 3% H 2 =balance N 2 gas annealing at 400 °C.…”
Section: Resultsmentioning
confidence: 99%
“…27) Lee et al also reported that the double (Pb 0.72 La 0.28 )Ti 0.93 O 3 (PLT) buffer layers that were inserted under and on PZT thin films (Au= PLT=PZT=PLT=Pt=Ti=SiO 2 =Si) conferred better resistance to the H 2 treatment. 28) In this study, we fabricated (Pb,La)(Zr,Ti)O 3 (PLZT) capacitors with various conductive AZO and Sn-doped In 2 O 3 (ITO) buffer layer thicknesses and top electrodes. Then, the ferroelectric properties, H 2 degradation characteristics, and fatigue properties of the AZO=PLZT=AZO=Pt and ITO= PLZT=ITO=Pt capacitors were evaluated.…”
Section: Introductionmentioning
confidence: 99%